NBTXR3, a first-in-class radioenhancer hafnium oxide nanoparticle, plus radiotherapy versus radiotherapy alone in patients with locally advanced soft-tissue sarcoma (Act.In.Sarc): a multicentre, phase 2–3, randomised, controlled trial. Issue 8 (August 2019) - Bonvalot, Sylvie; Rutkowski, Piotr L; Thariat, Juliette; Carrère, Sébastien; Ducassou, Anne; Sunyach, Marie-Pierre; Agoston, Peter; Hong, Angela; Mervoyer, Augustin; Rastrelli, Marco; Moreno, Victor; Li, Rubi K; et al.
Summary: Background: Pathological complete response to preoperative treatment in adults with soft-tissue sarcoma can be achieved in only a few patients receiving radiotherapy. This phase 2–3 trial evaluated the safety and efficacy of the hafnium oxide (HfO2 ) nanoparticle NBTXR3 activated by radiotherapy versus radiotherapy alone as a pre-operative treatment in patients with locally advanced soft-tissue sarcoma. Methods: Act.In.Sarc is a phase 2–3 randomised, multicentre, international trial. Adults (aged ≥18 years) with locally advanced soft-tissue sarcoma of the extremity or trunk wall, of any histological grade, and requiring preoperative radiotherapy were included. Patients had to have a WHO performance status of 0–2 and a life expectancy of at least 6 months. Patients were randomly assigned (1:1) by an interactive web response system to receive either NBTXR3 (volume corresponding to 10% of baseline tumour volume at a fixed concentration of 53·3 g/L) as a single intratumoural administration before preoperative external-beam radiotherapy (50 Gy in 25 fractions) or radiotherapy alone, followed by surgery. Randomisation was stratified by histological subtype (myxoid liposarcoma vs others). This was an open-label study. The primary endpoint was the proportion of patients with a pathological complete response, assessed by a central pathology review board following European Organisation for Research and Treatment of Cancer guidelines in the intention-to-treat population full analysis set. Safety analyses were done in all patients who received at least one puncture and injection of NBTXR3 or at least one dose of radiotherapy. This study is registered with ClinicalTrials.gov, number NCT02379845, and is ongoing for long-term follow-up, but recruitment is complete. Findings: Between March 3, 2015, and Nov 21, 2017, 180 eligible patients were enrolled and randomly assigned and 179 started treatment: 89 in the NBTXR3 plus radiotherapy group and 90 in the radiotherapy alone group. Two patients in the NBTXR3 group and one patient in the radiotherapy group were excluded from the efficacy analysis because they were subsequently discovered to be ineligible; thus, a total of 176 patients were analysed for the primary endpoint in the intention-to-treat full analysis set (87 in the NBTXR3 group and 89 in the radiotherapy alone group). A pathological complete response was noted in 14 (16%) of 87 patients in the NBTXR3 group and seven (8%) of 89 in the radiotherapy alone group (p=0·044). In both treatment groups, the most common grade 3–4 treatment-emergent adverse event was postoperative wound complication (eight [9%] of 89 patients in the NBTXR3 group and eight [9%] of 90 in the radiotherapy alone group). The most common grade 3–4 adverse events related to NBTXR3 administration were injection site pain (four [4%] of 89) and hypotension (four [4%]) and the most common grade 3–4 radiotherapy-related adverse event was radiation skin injury in both groups (five [6%] of 89 in the NBTXR3 group and four [4%] of 90 in the radiotherapy alone group). The most common treatment-emergent grade 3–4 adverse event related to NBTXR3 was hypotension (six [7%] of 89 patients). Serious adverse events were observed in 35 (39%) of 89 patients in the NBTXR3 group and 27 (30%) of 90 patients in the radiotherapy alone group. No treatment-related deaths occurred. Interpretation: This trial validates the mode of action of this new class of radioenhancer, which potentially opens a large field of clinical applications in soft-tissue sarcoma and possibly other cancers. Funding: Nanobiotix SA and PharmaEngine, Inc.